Clinical Enhancement in AI-Based Post-processed Fast-Scan Low-Dose CBCT for Head and Neck Adaptive Radiotherapy - Chen, Wen; Li, Yimin; Yuan, Nimu; Qi, Jinyi; Dyer, Brandon A.; Sensoy, Levent; Benedict, Stanley H.; Shang, Lu; Rao, Shyam; Rong, Yi (Frontiers in Artificial Intelligence, 2021)
Abstract Purpose: To assess image quality and uncertainty in organ-at-risk segmentation on cone beam computed tomography (CBCT) enhanced by deep-learning convolutional neural network (DCNN) for head and neck cancer. Methods: An in-house DCNN was trained using forty post-operative head and neck cancer patients with their planning CT and first-fraction CBCT images. Additional fifteen patients with repeat simulation CT (rCT) and CBCT scan taken on the same day (oCBCT) were used for validation and clinical utility assessment. Enhanced CBCT (eCBCT) images were generated from the oCBCT using the in-house DCNN. Quantitative imaging quality improvement was evaluated using HU accuracy, signal-to-noise-ratio (SNR), and structural similarity index measure (SSIM). Organs-at-risk (OARs) were delineated on o/eCBCT and compared with manual structures on the same day rCT. Contour accuracy was assessed using dice similarity coefficient (DSC), Hausdorff distance (HD), and center of mass (COM) displacement. Qualitative assessment of users’ confidence in manual segmenting OARs was performed on both eCBCT and oCBCT by visual scoring. Results: eCBCT organs-at-risk had significant improvement on the mean pixel value, SNR (P<0.05), and SSIM (P<0.05) compared to oCBCT images. The mean DSC of eCBCT-to-rCT (0.83±0.06) was higher than oCBCT-to-rCT (0.70±0.13). Improvement was observed for mean HD of eCBCT-to-rCT (0.42±0.13 cm) versus oCBCT-to-rCT (0.72±0.25 cm). The mean COM was less for eCBCT-to-rCT (0.28±0.19 cm) comparing to oCBCT-to-rCT (0.44±0.22 cm). Visual scores showed OAR segmentation was more accessible on eCBCT than oCBCT images. Conclusions: DCNN improved fast-scan low-dose CBCT in terms of the HU accuracy, image contrast, and OAR delineation accuracy, presenting potential of eCBCT for adaptive radiotherapy.